Family-led post-ICU discharge intervention for tracheostomized patients in India: Feasibility and formative impact evaluation - Swagata Tripathy; Asha P. Shetty; Upendra Hansda; Nanda KumarP; Alok Kumar Sahoo; Mahalingam V; Sujata Mahapatra; Jayanta Kumar Mitra; Parnandi Bhaskar Rao; Kasturi Sanyal; Itimayee Panda; Guruprasad N; et al. (PLoS ONE, 2026)
Background Survival after critical illness is increasing, but many patients remain chronically critically ill (CCI), dependent on tracheostomy and ongoing care. In low- and middle-income countries (LMICs), long-term facilities are scarce, costly, and often excluded from insurance, leading to prolonged ICU stays, hospital-acquired complications, and constrained bed capacity. Family-centred discharge interventions may provide a safe, cost-conscious alternative, but evidence on feasibility, acceptability, and implementation success in LMICs is limited. Methods We conducted a mixed-methods formative evaluation of the AIIMS ICU Rehabilitation (AIR) intervention, a co-designed, multi-component programme supporting the transition of tracheostomised patients from ICU to home care at a public tertiary hospital in India (2021–2024). The intervention comprised structured carer training, a mobile health communication platform, an equipment rental-retrieval bank, and post-discharge follow-up including home visits. Implementation outcomes were assessed using the Medical Research Council framework for complex interventions and the RE-AIM (Reach, Effectiveness, Adoption, Implementation, Maintenance) framework. Quantitative measures included validated implementation scales assessing acceptability, feasibility and appropriateness of the intervention, as well as carer confidence, quality of life and caregiver burden. Semi-structured interviews assessed stakeholder barriers and facilitations to implementation analysed using the Consolidated Framework for Implementation Research (CFIR). Results Of 762 patients screened, 314 were eligible and 300 dyads (96%) consented. Recruitment shifted from research-led to 98.5% clinician or family referral by year three. Carers and patients rated the intervention highly feasible, acceptable, and appropriate (median AIM 20, IAM 19.5, FIM 19.5), with greater endorsement than healthcare staff. Confidence improved with training: 66% of carers completed at least three structured training sessions and 61% achieved predefined competence after three training sessions. The mobile application was installed by 74% of dyads although WhatsApp was frequently preferred for communication with the care team. More than half accessed equipment through the rental–retrieval bank, and 91% of eligible families received in-person post-discharge follow-up. Qualitative findings identified barriers including carer reluctance in younger trauma cases, medicolegal concerns, fragmented training, and socioeconomic constraints. Facilitators included trust in clinicians, flexible training approaches, and ongoing post-discharge support. Conclusion The AIR intervention is feasible, acceptable, and adaptable in a public LMIC setting. Carer confidence increased during the intervention period and family-led home transition for tracheostomised ICU survivors was possible while identifying contextual barriers and facilitators relevant for scale-up. These findings informed refinement of the intervention, such as including targeted patient selection, early recruitment, and peer-supported training, and will guide a planned multicentre summative evaluation assessing effectiveness, sustainability, and cost-effectiveness.